2017
DOI: 10.1080/14992027.2017.1386331
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence-based interventions of dichotic listening training, compensatory strategies and combined therapies in managing pupils with auditory processing disorders

Abstract: The intervention groups were beneficial to pupils with APD and should be adopted by clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The increasing amount of research questioning the efficacy of dichotic testing is occurring alongside a growing interest in, and clinical application of, auditory training for dichotic deficits (Moncrieff et al, 2016;Osisanya and Adewunmi, 2018). For example, Moncrieff et al 2017investigated remediation of 125 children and adolescents aged 5-19 years diagnosed with amblyaudia and other binaural integration deficits.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing amount of research questioning the efficacy of dichotic testing is occurring alongside a growing interest in, and clinical application of, auditory training for dichotic deficits (Moncrieff et al, 2016;Osisanya and Adewunmi, 2018). For example, Moncrieff et al 2017investigated remediation of 125 children and adolescents aged 5-19 years diagnosed with amblyaudia and other binaural integration deficits.…”
Section: Introductionmentioning
confidence: 99%
“…With that, the DL task puts high demand on the core executive function of inhibition, which is the capacity to obstruct dominant responses and to suppress the influence of interfering information (e.g., Bexkens et al, 2015). The DL task has been applied to assess impairments within attention, working memory, and executive functions (Hugdahl, 2011) and found to be beneficial for participants with auditive, verbal, or neurological impairments (Helland et al, 2018;McCullagh and Palmer, 2017;Osisanya and Adewunmi, 2018). Apart from that, little research has been done with this task, but some evidence has indicated improvements in auditory attention and attentional control after 4 weeks of DL training (Soveri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%